2015
DOI: 10.1007/s00705-015-2446-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of IL28B.rs12979860 single-nucleotide polymorphism among Egyptian healthcare workers with and without a hepatitis C virus-specific cellular immune response

Abstract: The CC genotype of the interleukin (IL)-28B.rs12979860 gene has been associated with spontaneous hepatitis C virus (HCV) clearance and treatment response. The distribution and correlation of an IL28B.rs12979860 single-nucleotide polymorphism (SNP) with HCV-specific cell-mediated immune (CMI) responses among Egyptian healthcare workers (HCWs) is not known. We determined this relationship in 402 HCWs who serve a patient cohort with ~85% HCV prevalence. We enrolled 402 HCWs in four groups: group 1 (n = 258), sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
11
1
Order By: Relevance
“…This HCW remained seronegative and aviremic for more than a year of follow-up after transient viremia [ 90 ]. A similar observation was also documented among other HCW in Egypt [ 97 , 98 ]. These data suggest the exposure to and clearance of HCV infection without antibody seroconversion.…”
Section: Reviewsupporting
confidence: 88%
“…This HCW remained seronegative and aviremic for more than a year of follow-up after transient viremia [ 90 ]. A similar observation was also documented among other HCW in Egypt [ 97 , 98 ]. These data suggest the exposure to and clearance of HCV infection without antibody seroconversion.…”
Section: Reviewsupporting
confidence: 88%
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of portal hypertension was more in post-HCV (70%), HBV (4%), HCV, and HBV (8%), then Bilharizial periportal fibrosis (18%) [11,12]. There are 20 males and 30 females with no significant difference in the incidence of post-TIPS; there was no statistically significant difference as regards gender (p value 0.41) ( Table 1).…”
Section: Resultsmentioning
confidence: 94%